2019
DOI: 10.1016/s2214-109x(19)30202-5
|View full text |Cite
|
Sign up to set email alerts
|

Post-partum family planning in Burkina Faso (Yam Daabo): a two group, multi-intervention, single-blinded, cluster-randomised controlled trial

Abstract: Background Post-partum family planning services can prevent maternal and child morbidity and mortality in lowresource settings. We assessed the effect of a family planning intervention package on modern contraceptive use at 12 months post partum in predominantly rural Burkina Faso. Methods Yam Daabo was a two group, multi-intervention, single-blinded, cluster randomised controlled trial. Primary health-care centres were randomly allocated to intervention or control clusters in a 1:1 ratio with only data analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 20 publications
2
26
2
3
Order By: Relevance
“…2 In response, the Yam Daabo trial (meaning "your choice" in Mooré, one of the local languages in Burkina Faso) was designed to test the effectiveness of a low-technology, postpartum family planning intervention package, established using participatory action research, on contraceptive uptake. 9 In predominantly rural settings in Burkina Faso, results showed that the use of modern contraceptives almost doubled at 12 months post partum, reaching 55% of women in the intervention group versus 29% of women who received routine care in the control group (adjusted prevalence ratio 1•79, 95% CI 1•30-2•47). 9 Significant differences were also found in the proportion of women in the two groups using long-acting contra ceptives, mostly implants (29% vs 17%), and short-acting methods (26% vs 12%), with injectables prevailing.…”
Section: Introductionmentioning
confidence: 99%
“…2 In response, the Yam Daabo trial (meaning "your choice" in Mooré, one of the local languages in Burkina Faso) was designed to test the effectiveness of a low-technology, postpartum family planning intervention package, established using participatory action research, on contraceptive uptake. 9 In predominantly rural settings in Burkina Faso, results showed that the use of modern contraceptives almost doubled at 12 months post partum, reaching 55% of women in the intervention group versus 29% of women who received routine care in the control group (adjusted prevalence ratio 1•79, 95% CI 1•30-2•47). 9 Significant differences were also found in the proportion of women in the two groups using long-acting contra ceptives, mostly implants (29% vs 17%), and short-acting methods (26% vs 12%), with injectables prevailing.…”
Section: Introductionmentioning
confidence: 99%
“…One effort that can be done is to maximize the role of competent agencies or agencies in dealing with population growth (Kelsen, 2010). In the process of minimizing population growth, it must be done in several stages that have been formatted so well that it can be carried out and run well because at any time population growth can change (Tran et al, 2019). To minimize population growth in Indonesia, one can be done with family planning (KB) programs that have been carried out by the government (Woo, Alamgir, & Potter, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To improve the use of postpartum contraceptive methods, in 2015, we implemented a set of interventions in two African countries, Burkina Faso (BF) and the Democratic Republic of the Congo (DRC), and tested them in a cluster-randomized trial called Yam Daabo described previously [ 2 , 3 ]. The main results showed a significant increase in the use of contraceptive methods among women receiving interventions compared to women in the control group in both countries [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%